Mobile Game-Based Learning Application Integrating Playability to Address Challenges in Learning Cell Division Among Secondary School Biology Students - Han Cheng, Low (Universiti Malaysia Sarawak, 2025)
STEM education is a key agenda for transforming the education system to produce students equipped with 21st-century skills to tackle the challenges of the modern world. Among STEM subjects, Biology is recognized as one of the most challenging to learn and teach. Within Biology, Cell Division is considered one of the most difficult topics, according to previous studies. Therefore, it is essential to develop innovations that help students to overcome the difficulties of learning Cell Division and enhance their learning process. Given the widespread ownership of mobile phones among students and the flexibility of mobile learning, mobile game-based learning (mGBL) presents a promising solution to address these challenges. In this study, a design-based research (DBR) approach was adopted, which consisted of two main phases. The first phase was a preliminary study to diagnose learning difficulties and identify design requirements, and the second phase involved the design, development, and testing of an mGBL application in collaboration with Biology teachers. A preliminary study was conducted, involving online interviews with three Biology teachers and self-administered questionnaires with thirty-one Form 4 students, to identify the challenges in learning Cell Division topic from both students’ and teachers’ views. The results revealed that students struggled with the topic due to cognitive, motivational, affective, social, and other challenges. Cognitive challenges were the most dominant, with students having difficulty memorizing content, distinguishing between similar terms, and understanding abstract concepts. The preliminary study also identified strategies suggested by both students and teachers to improve learning, including the use of games, visual aids, memory tools, and collaborative learning methods. Based on the findings from the preliminary study, an online mGBL application called Cell% was developed using the Flow Framework for Educational Games as the design framework and the mGBL Engineering Model as the development methodology. After development, Cell% was implemented in Biology classes for approximately two weeks to assist teachers in teaching Cell Division. Data collection involved questionnaires with three Biology teachers and forty-two Form 4 students to evaluate the playability of Cell% and its effectiveness in addressing the learning challenges identified in the preliminary study. The findings showed that Cell% had high playability and effectively addressed all learning challenges, with overall ratings ranging from 3.67 to 4.45 out of 5, especially in cognitive and affective aspects. However, its effectiveness in addressing social challenges was lower, indicating room for improvement in enhancing Cell% in this area. Additionally, feedback from students and teachers revealed general satisfaction with Cell%, though some suggested technical improvements, particularly in bug fixes, gameplay enhancements, and additional features. This study exemplifies the use of multi-perspective, problem-based game design in game-based learning, introducing a novel approach in game-based learning studies for Cell Division learning.